2020
DOI: 10.1080/17425247.2021.1829590
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled cytotoxic chemotherapy: clinical challenges, recent developments, and future prospects

Abstract: Introduction: Since 1968, inhaled chemotherapy has been evaluated and has shown promising results up to phase II but has not yet reached the market. This is due to technological and clinical challenges that require to be overcome with the aim of optimizing the efficacy and the tolerance of drug to reopen new developments in this field. Moreover, recent changes in the therapeutic standard of care for treating the patient with lung cancer also open new opportunities to combine inhaled chemotherapy with standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 147 publications
(364 reference statements)
0
51
0
Order By: Relevance
“…Last but not least, the administration of a nebulized CIS solution, during a phase I study, showed that the targeted dose was not reached following >6 h of nebulization (Wittgen et al, 2007). Besides, this involved heavy equipment (closed cabin, negative pressure rooms, high efficiency particulate air-HEPA filters) to limit the environmental contamination and exposure of the medical staff (Wauthoz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last but not least, the administration of a nebulized CIS solution, during a phase I study, showed that the targeted dose was not reached following >6 h of nebulization (Wittgen et al, 2007). Besides, this involved heavy equipment (closed cabin, negative pressure rooms, high efficiency particulate air-HEPA filters) to limit the environmental contamination and exposure of the medical staff (Wauthoz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one strategy to overcome these limitations was to develop a CIS dry powder for inhalation (DPI) formulation (CIS-DPI) with controlled cisplatin release and with sustained lung retention to increase the exposure of the lung tissue and therefore of the lung tumour to the drug (Wauthoz et al, 2020). CIS-DPI has been previously developed using solid lipid microparticles embedding CIS into a lipid matrix (Amighi et al, 2020;Levet et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various research studies are going on to develop effective pulmonary formulations (DPIs, pMDI, and nebulizer) to target local pulmonary as well as systemic diseases. It has been reported that about 75% of drugs are under research and development, and about 40% of pulmonary formulations are in market for the treatment of various pulmonary as well as systemic diseases [ 225 ]. Marketed DPIs formulations for clinical use are listed in Table 3 .…”
Section: Factors Influencing the Clinical Efficacy And Marketed Fomentioning
confidence: 99%
“…The addition of localized delivery to the systemic delivery could allow a therapeutic intensification due to a loco-regional diffusion of the drug close to the tumour, while fighting invasive and diffuse cancerous cells [11][12][13]. The pulmonary route as localized delivery for lung cancer therapy is promising as it may limit systemic exposure to chemotherapy and related severe systemic toxicities [13,14]. Pulmonary delivery allows high local drug concentrations and low systemic exposure, with a possibility to increase the frequency of administration of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A high frequency of administration, i. e., several administrations per week, will only be feasible for as long as inhaled chemotherapy is well-tolerated in the lungs. The chemotherapy candidate and its formulation is therefore crucial to the development of this approach [13]. Cisplatin is a promising chemotherapy candidate due to its central position in lung cancer treatment and its good safety profile in the lungs, observed after nebulization to up to phase II [15].…”
Section: Introductionmentioning
confidence: 99%